2014
DOI: 10.1128/aac.02565-14
|View full text |Cite
|
Sign up to set email alerts
|

Limited Activity of Clofazimine as a Single Drug in a Mouse Model of Tuberculosis Exhibiting Caseous Necrotic Granulomas

Abstract: New drugs and drugs with a novel mechanism of action are desperately needed to shorten the duration of tuberculosis treatment, to prevent the emergence of drug resistance, and to treat multiple-drug-resistant strains of Mycobacterium tuberculosis. Recently, there has been renewed interest in clofazimine (CFZ). In this study, we utilized the C3HeB/FeJ mouse model, possessing highly organized, hypoxic pulmonary granulomas with caseous necrosis, to evaluate CFZ monotherapy in comparison to results with BALB/c mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
106
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(111 citation statements)
references
References 46 publications
(57 reference statements)
4
106
1
Order By: Relevance
“…Of the three types of microbial populations tested, the slowly replicating biofilmproducing bacilli of both mycobacterial species were found to be most susceptible to These findings are essentially in agreement with a recent study reported by Irwin et al who described the differential efficacy of clofazimine monotherapy in several murine models of experimental pulmonary TB [24]. Clofazimine was found to be most effective against the rapidly growing, intracellular bacilli in multifocal, coalescing lesions in the lungs of BALB/c mice as well as extracellular bacilli in the initiation phase of granuloma formation in C3HeB/FeJ mice [24].…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…Of the three types of microbial populations tested, the slowly replicating biofilmproducing bacilli of both mycobacterial species were found to be most susceptible to These findings are essentially in agreement with a recent study reported by Irwin et al who described the differential efficacy of clofazimine monotherapy in several murine models of experimental pulmonary TB [24]. Clofazimine was found to be most effective against the rapidly growing, intracellular bacilli in multifocal, coalescing lesions in the lungs of BALB/c mice as well as extracellular bacilli in the initiation phase of granuloma formation in C3HeB/FeJ mice [24].…”
Section: Discussionsupporting
confidence: 80%
“…The findings of the current study taken together with those of Irwin et al [24] and others [16,25] suggest that clofazimine and other antimycobacterial agents may be most effective in well aerated environments, seemingly consistent with the involvement of endogenously generated reactive oxygen species in antimicrobial activity. However, alternative mechanisms of clofazimine-mediated antimicrobial activity, probably also negated by dormancy, have also been proposed [15,19].…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…Together with prior studies indicating the poor activity of PZA in large caseous lesions (9,22), this study demonstrates the potential value of this heterogeneous disease model for identifying more precisely the lesion microenvironments in which certain drugs exert their activity and contribute to the efficacy of combination therapy. Strategies to increase the proportion of C3HeB/FeJ mice with large caseous lesions are under investigation.…”
Section: Discussionmentioning
confidence: 93%
“…[350][351][352] However, in C3HeB/FeJ mice that develop large caseous granulomas, clofazimine is less effective, perhaps because of the hypoxic conditions or reduced diffusion through caseous tissue, or both. 353,354 Clofazimine shows no bactericidal activity in patient sputum over the first 14 days of treatment. 355 However, in a phase 2 clinical trial, adding clofazimine at a dose of 100 mg daily for 21 months to multidrug background therapy (ie, the MDR tuberculosis treatment regimen) improved MDR tuberculosis treatment success versus placebo (74% vs 54%).…”
Section: Clofaziminementioning
confidence: 99%